Gambaran self-compassion perawat instalasi gawat darurat di Jakarta - Adinda, Puspa Triani; Aryanto, Christ Billy; Tunjungsari, Laurensia Harini (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
This study aims to explore how self-compassion shapes the experience of hospital nurses in Emergency Department (ED) in Jakarta. Previous studies demonstrated that the lack of self-compassion can increase compassion fatigue, thereby reducing the quality of services and eventually affect patients’ well-being. Mixed-methods design was employed by collecting data from 77 nurses through convenient sampling. Two nurses with highest self-compassion scores and a nurse with lowest self-compassion score were interviewed for further analysis. The descriptive result indicated that self-compassion of ED nurses in Jakarta was considerably high and only one nurse had relatively low self-compassion. There was a significant difference in self-compassion based on working time and hospital types. Qualitative analysis indicated that under stressful circumstances, nurses with high self-compassion tended to engage with various religious activities, while the one with low self-compassion tended to be self-indulging.